World watch geography Book 2 A geography course for grade 7 - Moorcroft, Christine (Karachi: Oxford University press, 2023)
It is revised according to the national curriculum of Pakistan. It integrated physical, human, and environmental geography with a special focus on Pakistan. It is for lower secondary level.
Keywords: Geography, grade 7